The academic and non-academic factors related to students' subject failing at the school of arts and sciences of the university of El Salvador, semester I 2000 - González Mina, Katya Valeria; Santamaria Chicas, Loren Beatriz; Landaverde Castillo, Manuel Alexander; Machado Quintanilla, María de los Angeles; Mendoza Galvez, Oscar Rolando; Blandón de Castro, Norma Cecilia (Universidad de El Salvador, 2003)
The phenomenon of failing subjects as an issue of concern for all educational institutions regardless of the rate it may reach, for the fact that if it exists, it demands the quality of the processes and programs that educational institution offers; the quality of its teachers and the particular characteristics of every student. For this reason the following research comprises a wide view of the possible causes that are related with the issue of failing subjects.